163 Genetic Modifiers in Carriers of the SCN5A E1784K Mutation with Variable Phenotypic Expression - Long QT3 / Brugada Syndrome Overlap Disease. (31st May 2014) - Dullewe Wijeyeratne, Yanushi; Muggenthaler, Martina; Tanck, Michael W; Schott, Jean-Jacques; Kyndt, Florence; Probst, Vincent; Borggrefe, Martin; McKeown, Pascal; Veltmann, Christian; Crotti, Lia; Schwartz, Peter; Sharma, Sanjay; et al.
Abstract : Introduction: Long QT syndrome (LQTS) and Brugada syndrome (BrS) are inherited arrhythmia syndromes characterised by sudden death and highly variable penetrance. The E1784K mutation in SCN5A, which encodes the α-subunit of the cardiac sodium channel Nav1.5, is the most commonly identified SCN5A mutation in both conditions. It causes a LQTS/BrS overlap disease with variable phenotype. The aim of this project was to identify potential genetic modifiers that may influence the E1784K phenotypic expression in an international cohort of carriers of this mutation. Methods: 88 E1784K mutation carriers from 14 families were genotyped for 48 single nucleotide polymorphisms (SNPs). The chosen SNPs associate with different electrocardiographic (ECG) traits in the general population in large genome wide association studies. Association with PR interval, QRS duration, QTc interval, BrS phenotype (spontaneous and drug-induced type 1 ECG pattern) and time to occurrence of symptoms/arrhythmic events were tested using either mixed effects Cox models or generalised estimating equation logistic regression tests as appropriate, with adjustment for age and sex. P-values were uncorrected for multiple testing as the aim of this study was to identify potential genetic modifiers with existing evidence for biological plausibility that could be subsequently confirmed or refuted through replication in larger patient cohorts. Results: Eight SNPs showed significant association (p < 0.05) with PR interval, with effect sizes (change per minor allele) of -21.7 to +15.5 ms. Two SNPs were significantly associated (p < 0.05) and one SNP was highly significantly associated (p = 0.0022, rs251253, Chr 5) with QRS duration, with effect sizes of -5.9 to +8.2 ms. Three SNPs showed significant association with QTc duration (p < 0.05) with effect sizes of +11.9 to +13.4 ms. Four SNPs were significantly associated (p < 0.05) and two SNPs (rs11848785, Chr 14 and rs10919035, Chr 1) were highly significantly associated (p < 0.005) with the BrS. Two SNPs (rs11047543, Chr 12 and rs17020136, Chr 2) were associated with the occurrence of events (cardiac syncope, ventricular tachycardia or aborted cardiac arrest) with p-values of 0.0467 and 0.0154, and odds ratios of 3.35 and 2.61 respectively. Conclusions: Several SNPs showed significant and highly significant association with different ECG traits and occurrence of symptoms in this cohort of E1784K carriers. These results provide promising initial evidence for the presence of potential genetic modifiers in LQT3 and BrS. Further supporting evidence will be required through replication in larger cohorts and functional studies. These may provide evidence for new pathways that modulate phenotype and risk and provide clinical risk stratifiers.